The Pole of Event: Bibikhin and Phenomenology - Kosykhin, Vitaly (Stasis, 2015)
The article investigates the question of Bibikhin’s position on phenomenology. Based on the existence of two different phenomenological projects—those of Husserl and Heidegger—the author identifies two poles that concentrate main phenomenological problems: the pole of event and the pole of contemplation. Their interconnectedness, though never direct, is reflected in the fact that when the one pole comes to light, the other is automatically hidden in its shadow. Vladimir Bibikhin, together with Heidegger and Wittgenstein, is considered a thinker of the pole of event. The pole of contemplation is presented by Alexey Losev, Husserl and Derrida.